E-Farm Livestock Platform Requirements Engineering Using Loucopoulos and Karakostas Iterative Process Model - Liana Trihardianingsih; Maie Istighosah; Ariel Yonatan Alin; Muhammad Ryandy Ghonim Asgar (International Journal of Innovation in Enterprise System, 2024)
Global human population growth has forced farms to evolve in order to produce more livestockproducts more efficiently while also paying attention to public health, environmental sustainability,and animal welfare. However, problems arise when some diseases appear to affect farm animals andlarge companies providing livestock products dominate the market. It is necessary to develop aplatform or application that can be used to solve these two problems, especially for breeders who havefarms on a small scale. This study aims to outline the process of understanding engineeringrequirements by utilizing the Loucopoulos and Karakostas Requirements Engineering Process Modelmethod, which consists of elicitation of requirements, specification of requirements, as well asvalidation and verification of requirements. The development process is carried out by hiring breedersand potential customers to determine the priority needs of the platform. The results showed that of the25 defined functional needs, there were 22 final functional needs that were validated with valuesabove 50%. The E Farm platform should be further developed based on the defined demands since atotal of 22 validated needs have been determined to be able to represent 88% of the needs required byusers.